Rare occurrence of type 2 diabetes mellitus in patients with sickle cell anaemia: assessing the contribution of inflammation, insulin resistance and glucose buffering capacity of abnormal haemoglobin - Rahamon, Sheu Kadiri; Ogundeji, Sunday Peter; Olerimi, Samson Eshihokhale; Akinlade, Kehinde Sola (Journal of Medical Science, 2022)
This review was designed to discuss the rare occurrence of diabetes mellitus (DM) in patients with sickle cell anaemia (SCA) with a particular focus on factors, such as life expectancy, body weight, chronic inflammation, insulin resistance, glucose buffering property of haemoglobin, and microRNAs (miRNAs), aiming to stimulate research which will fill the existing knowledge gaps regarding the interplay between SCA and DM. Additionally, possible pharmacotherapeutic approaches to DM were also highlighted in the review. Google Scholar and PubMed search engines were used to search for the relevant keywords, such as sickle cell trait, sickle cell disease, sickle cell anaemia, insulin resistance, and diabetes mellitus. SCA patients appear to have β-cell dysfunction with a reduced insulin secretion, but present a similar insulin sensitivity status as other patients without haemoglobinopathy. Glucose buffering property of haemoglobin and the possible DM-protective roles of miRNAs in the sickled erythrocytes constitute some of the potential factors protecting SCA patients from developing DM. Sickle cell anaemia is associated with several complications and endocrinopathies, nevertheless, its coexistence with DM continues to be a rare observation. Proper elucidation of the mechanisms which seemingly confer ‘protection’ against DM in patients with SCA may provide some therapeutic insights regarding DM.